(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
The kinds of paper were changed in different periods in Central Asia. The masters used good raw material and invented new kinds of paper. Country’s economical – cultural life influenced the invention of some kinds of paper. The investigators said that there were 3 kinds of paper in Samarkand. The superior paper was made from silk and it was very beautiful, smooth and light – yellow. This paper was very delicate and local people called it “silken paper”.